BNIP3 promotes the motility and migration of keratinocyte under hypoxia. Issue 5 (2nd March 2017) - Zhang, Junhui; Zhang, Dongxia; Yan, Tiantian; Jiang, Xupin; Zhang, Can; Zhao, Liping; Li, Lingfei; Tang, Di; Zhang, Qiong; Jia, Jiezhi; Zhang, Jiaping; Huang, Yuesheng
Abstract: The migration of keratinocytes from wound margins plays a critical role in the re‐epithelialization of skin wounds. Hypoxia occurs immediately after injury and acts as an early stimulus to initiate the healing processes. Although our previous studies have revealed that hypoxia promotes keratinocyte migration, the precise mechanisms involved remain unclear. Here, we found that BNIP3 expression was upregulated in hypoxic keratinocytes, and BNIP3 silencing suppressed hypoxia‐induced cell migration. Additionally, hypoxia activated the focal adhesion kinase (FAK) pathway through upregulation of BNIP3, while FAK inhibition attenuated hypoxic keratinocyte migration. Here, we conclusively demonstrate a novel role for BNIP3 in hypoxia‐induced keratinocyte migration. Furthermore, we provide a new perspective on the molecular mechanisms of wound healing and identify BNIP3 as a potential new molecular target for clinical treatments to enhance wound healing.